Facile one-step microwave-assisted modification of kaolinite and performance evaluation of pickering emulsion stabilization for oil recovery application. (15th May 2019) - Mo, Songping; Pan, Ting; Wu, Fan; Zeng, Minxiang; Huang, Dali; Zhang, Lecheng; Jia, Lisi; Chen, Ying; Cheng, Zhengdong
Abstract: A facile one-step microwave-assisted method was proposed for kaolinite intercalation and grafting. The structure, morphology, composition, and size distribution of kaolinite sheets were investigated using various methods, including X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, and thermogravimetric (TG) analysis. The potential application of the modified kaolinite as an oil/water emulsion stabilizer was studied. The results verified that intact kaolinite sheets were obtained. The dodecane/water emulsion stabilized by the modified kaolinite remained stable for more than 60 days. The effective performance suggests that the effectiveness of the proposed kaolinite modification method may be useful for Pickering emulsion stabilization in oil recovery applications. Highlights: A facile one-step microwave-assisted method was proposed for modifying kaolinite. Intact modified kaolinite platelets were obtained for emulsion stabilization. The modified kaolinite was verified to be an efficient emulsion stabilizer. The modified kaolinite has great potential for application in oil recovery.